Cuerpo y educación en Nietzsche. Los personajes pedagógicos como mecanismo de transformación (2011)
ABSTRACT: The aim of this paper is to interpret the concept of body and education in the work of Nietzsche for a Body Education in light of Pedagogical Anthropology. The approach is hermeneutical and theoretical-documentary. As a result, it appears that the body is the theme of the interpretations, a field of competitive forces that struggle for the preservation or creation of new values. From a critical perspective, education is understood as bodily strength leveling sponsored by the belief in absolute truth. From one perspective, yes, education transforms the body while providing many opportunities for liaison with elements of both culture and nature, spreading a fixed idea of man. Furthermore, we interpret the idea of taste as a way of interaction of the body with the world, through the opening and self-defense as each perception may strengthen or weaken. The taste, unlike Kant, is concerned, which implies a radical critique of the distinction between art, science and morality raised in the Critique of Judgement. The investigation can be concluded that an educational strategy is the construction and testing of pedagogical characters that expand / update the limits set by the logic of identity.